Collaborative office document editing and revision control - Shen, Haifeng. (2009)
The aim of this project is to research innovative technologies to support collaborative editing of office document. The deliverables are a package of technologies and prototype systems that support unconstrained interaction and flexible revision control. There search methodology is a combination of theoretical and experimental approaches, where theoretical approaches include modelling, algorithm design and analysis and experimental approaches include design, implementation, andevaluation working prototype systems. Major accomplishments include a package of protocols and algorithms to enable unconstrained interaction, a complete merging algorithm and a syntactic merging algorithm for merging of parallel versions of text documents, a number of research prototypes to verify and demonstrate research results including CoWrite, CoImpress, CoCalc, CoFCKeditor, CoEclipse, CoRSA, andCoMaya,and an accessgrid environment integrated with collaborative office production applications. The research work done in this project has advanced scientific frontiers by contributing a package of innovative technologies that can enable unconstrained interaction in conducting collaborative editing of office documents and a novel transparent adaptation approach that can transparently add these technologies into existing office productivity applications or other applications.